PERAN KELEMBAGAAN LOKAL TERHADAP NILAI KEARIFAN TRADISIONAL DALAM PEMANFAATAN DAN PELESTARIAN SUMBERDAYA PESISIR (Studi Kasus di Desa Panglima Raja Kecamatan Concong Kabupaten Indragiri Hilir Propinsi Riau) - Zulkarnain ' (Berkala Perikanan Terubuk, 2010)
The research was conducted in Panglima Raja Village ConcongSubdistrict Indragiri Hilir Regency of Riau Province. It was aimed to identify ofrule institution that relationship with local wisdom. The research was done by casestudy or gounded research method.The result of research showed that there were no rule of custom institutionto exploiting and conservation of coastal zone resources in Panglima RajaVillage. The rule of village government institution as decision maker to legality oflocal wisdom value. But not yet maximum to legalize value, norm of localwisdom in society Panglima Raja Village become law of legal formal, becouse themake of rule do not acomodation participatory local wisdom.